The decrease of intraflagellar transport impairs sensory perception and metabolism in ageing - Yincong Zhang (Nature Portfolio, 2021)
Sensory perception and metabolic homeostasis are known to deteriorate with ageing, while mechanisms underlying their deterioration remain poorly understood. Here, the authors demonstrate that decrease of intraflagellar transport in the cilia of sensory neurons impairs sensory perception and metabolism in ageing C. elegans.